Pengaruh Kepemimpinan, Motivasi, Lingkungan Kerja Terhadap Kinerja Karyawan Rindang Coffe And Eatery Palembang - Ridwan Ahmad Tri Ananda; Fauziah Afriyani; Muhammad Bahrul Ulum (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of leadership, motivation and work environment on employee performance at Rindang Coffee and Eatery Palembang. This research was carried out using quantitative analysis and involved 50 respondents, based on the results showing that both leadership, motivation and work environment affect employee performance partially or simultaneously. Testing in the research was carried out through partial tests, simultaneous tests, and coefficient of determination in SPSS version 25, the results of partial testing showed that leadership (X1), Motivation (X2) were significant on Employee Work Performance at Indang Coffee And Eatery Palembang, with respective Tcounts -respectively 1.907 and 2.707 (THcount > TTable 1.679) and Work Environment (X3) Ts 3.012 (THcount > TTable 1.679) and for the test together, FCount 619.051 (FCount > FTable 3.132) this shows that there is a positive and significant influence on employee work performance.